Classroom Practice: Applying The Scientific Approach Based on The 2013 Curriculum - Usman Kasim; Teuku Zulfikar; Nasriati Nasriati (English Education Journal, 2017)
This study was done to find out about the implementation of the scientific approach based on the 2013 Curriculum. The subjects of this research were two English teachers of second year classes at SMA Negeri 1 Bireuen. The implementation of the scientific approach follows five learning experience called observing, questioning, associating, experimenting, and communicating. The classroom activities must accomodate all 5 items actualized in three dimensions viz: the dimension of teaching plans, the dimension of teaching processes, and the dimension of teaching evaluation. Data was collected through classroom observations and interviews and was analyzed descriptively. Related to the dimension of teaching plans, the teachers did not prepare well before running the teaching processes. Their lesson plans did  not match the frame work recommended by the rule of Minister of Education and Culture/Permendikbud no.81.A 2013 as required by the 2013 curriculum. Related to the dimension of teaching process: The teachers used the steps of the scientific approach viz: observing, questioning, associating, experimenting, and communicating. But the conduct was not perfect, the teachers missed some aspects, and they did not run the teaching process according to  the rules that are in Permendikbud no.81.A 2013. In relation to the dimension of evaluation, the evaluations used non-authentic assessments that gave the biggest  emphasis to the cognitive domainwhich  differred  from the mandate for the 2013 curriculum in Permendikbud no. 81A 2013.